Culture based on local wisdom ide to malaqbi and public services: The mediating role of employee performance - Visi Denok Mustikasari; Bambang Supriyono; Riyanto Riyanto; Wike Wike (Cita Konsultindo Research Center, 2024)
This study investigates the important role of the implementation of local wisdom-based culture ide to malaqbi, the performance of the apparatus, on the quality of public services at the One-Stop Integrated Services and Investment Service or DPMPTSP in four different districts in the midst of improving public services. The novelty of this research lies in the adoption of the local culture of the Mandar tribe based on the Regulation of the Governor Sulawesi Barat to overcome the problems faced by the agency. Apart from that, the five-point Likert scale survey targets people who have processed licensing and non-licensing letters at DPMPTSP. Data from 200 respondents was analyzed to determine the relationship between variables. The results of the research show that all the variables studied, namely the implementation of local cultural ide to malaqbi and the performance of the apparatus, can directly improve the quality of public services. The mediating effect of apparatus performance can also improve the relationship between the implementation of local culture and ideas to transform into a work culture for public services. This means that the more disciplined the apparatus is in working, the more innovative the apparatus is in completing its tasks, and the higher the work ethic of the apparatus and the more performant the apparatus is, the higher the quality of service that will be provided to the community as service users.